Cross-cultural adaptation of Chinese international students: Effects of distant and close support-seeking - Zheng, Shaofeng; Ishii, Keiko (Frontiers in Psychology, 2023)
Social support-seeking is considered to be an effective way for international students to cope with their acculturative stress and contribute to cross-cultural adaptation. In addition to support from people in the host country (close support), the ease of online communication now allows international students to receive additional support from people back in their home country (distant support). However, little research has investigated whether distant support works as effectively as close support. In two studies, we examined the differential effect of distant and close support-seeking on the psychological adaptation of Chinese international students in the host country and how acculturation orientations relate to the use of these two types of support. Chinese international students in Japan (Study 1; N = 172) and the United States (Study 2; N = 118) completed an online survey that assessed participants’ host/home culture orientation, distant emotional/instrumental support-seeking, close emotional/instrumental support-seeking, and psychological adaptation. Results showed that distant emotional support-seeking negatively predicted psychological adaptation in the host country. Nevertheless, distant emotional support-seeking alleviated feelings of loneliness in Chinese international students as close emotional support-seeking did (Study 2). Also, the results showed that international students with higher home-culture orientation sought more distant support, whereas those with higher host-culture orientation sought more close support. Further, Chinese-culture orientation increased distant emotional support-seeking, decreasing psychological adaptation as well as loneliness. These findings highlight the importance of considering the source and types of support when discussing the implications of social support for the cross-cultural adaptation of international students.